EventWeb: Developing a Human-Centered Computing System. - Jain, Ramesh (Computer (00189162), 2008)
The article discusses EventWeb, a human-centered computing system (HCC). Computers have been evolving since they were first created to mimic the analytical abilities of humans, first as calculators and then as electronic computers with advanced processing, storage, communication, and other related areas. HCC ranges across aspects of computing from human computer interfaces to virtual reality systems with a focus on the quality of content. Changes in the evolution of computing has included input and output, applications, and user expectations.